(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
The connection of legal psychology with other sciences is an interesting question of study. Legal psychology is one of the important areas of its “mother” science – psychology. There are a number of disciplines similar to legal psychology that L.S. Vygotsky called them “branches of applied psychology.” This is medical, educational psychology, etc. For example, the section of social psychology, which studies socio-psychological problems of the individual, is the basis for the work of an investigator in identifying psychological characteristics. Educational, medical and engineering psychology also serve as the basis for many provisions of legal psychology.